Religious studies specification A Christianity, Islam, Judaism and the religious, philosophical and ethical themes - Parry, Lesley; Hayes, Jan; Butler, Sheila (Hachette Learning, 2025)
Trust the experts; let subject specialists with examining experience provide you with a comprehensive, creative and time-efficient teaching pathway through AQA Specification A updated for exams from 2026 onwards.